Epidemiology and Characteristics of North American Crotalid Bites Reported to the National Poison Data System 2006–2020. Issue 12 (December 2022) - Thornton, Stephen; Darracq, Michael
Abstract : North American pit viper, or crotalid, bites remain a low-incidence and potentially high-consequence medical event. This study investigated the epidemiology and characteristics of crotalid bites reported to all poison control centers in the United States from 2006 to 2020 and would be the largest study of North American crotalid bites in the medical literature. Abstract: Objectives: North American pit viper, or crotalid bites, remain a low-incidence and potentially high-consequence medical event. Although the venom of these snakes is known to cause tissue, hematologic, and neurologic toxicity, the published literature on North American crotalid bites remains limited. The National Poison Data System, the data repository for the 55 poison control centers in the United States, offers a unique opportunity to examine nationwide trends involving venomous snake bites. Methods: National Poison Data System cases involving North American crotalids from 2006 to 2020 were analyzed. Data collected included age and type of snake, date, geographic location, pertinent clinical characteristics, treatments administered, and medical outcomes including incidence of "dry" bites and death. Results: A total of 55, 914 cases were identified during the 15-year study period. Cases, especially those involving copperheads, increased during the study period. Most of the cases were reported in July. Cases were reported in all 50 states and Washington, DC, with Texas having the most cases (n = 9115). North Carolina had the largest increase in bites during the study period. Moderate or major medical outcomes were documented in 58% (n = 32, 584) of cases, with 25% (n = 14, 195) being admitted to a critical care unit. Puncture wound, edema, and pain were the most commonly documented symptoms. Antivenom was documented as being administered in 25% (n = 14, 151) of cases. Dry bites were reported in <1.5% of cases. Thirty-two deaths were reported, 23 involving rattlesnakes. Conclusions: This study demonstrates that reported North American crotalid bites appear to be increasing over time and are associated with potentially significant morbidity. Mortality, however, remains low.